2020
DOI: 10.1016/j.jasc.2020.07.133
|View full text |Cite
|
Sign up to set email alerts
|

Are CIN3 risk or CIN3+ risk measures reliable surrogates for invasive cervical cancer risk?

Abstract: Highlights Discuss ASCCP guideline. CIN3 reliable surrogates for cervical cancer? The Pittsburgh Cervical Cancer Screening Model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Our model also suggested that 13–14/34 (38–41%) cases of HSIL with “risk biomolecules” (3.95–4.23) might progress to cervical cancer. This is in broad agreement with the findings by Austin (2020), wherein they determined that only around 30% of CIN 3 lesions would progress to cervical cancer in 30 years [ 65 ]. However, this study found that slides suffer from issues such as the positions of the biopsies.…”
Section: Discussionsupporting
confidence: 92%
“…Our model also suggested that 13–14/34 (38–41%) cases of HSIL with “risk biomolecules” (3.95–4.23) might progress to cervical cancer. This is in broad agreement with the findings by Austin (2020), wherein they determined that only around 30% of CIN 3 lesions would progress to cervical cancer in 30 years [ 65 ]. However, this study found that slides suffer from issues such as the positions of the biopsies.…”
Section: Discussionsupporting
confidence: 92%
“…We focused our discussion specifically on the differential detection of cancer because it is the primary disease state that all screening approaches seek to avoid. 2 As with all aspects of laboratory medicine, no test is perfect, and tests must be ordered and interpreted in the appropriate circumstances.…”
Section: The Authors’ Replymentioning
confidence: 99%
“…Several studies in Europe and fewer in the United States have demonstrated the higher sensitivity of HPV in comparison with cytology in detecting CIN3 and CIN3+. However, many cases of CIN3 will not progress to cancer, and thus HPV testing could potentially lead to overdetection of nonprogressive lesions 10 . Most trials have fewer cases of invasive cancer to analyze, so we are left with less data proving the superiority of HPV testing over cytology in the detection of invasive cancers.…”
mentioning
confidence: 99%
“…Invasive cancer morbidity and mortality are recognized as key outcome measures in judging the effectiveness of any cancer screening program. As Austin et al stated, invasive cervical cancer risk, morbidity, and mortality “can unfortunately only be measured based on data from long‐term observational studies.” 10 The ACS guidelines also relied on modeling data that may not reflect the largely opportunistic instead of organized screening methods in the United States. CIN3+ specimens have HPV‐negative results approximately 10% of the time; several studies have shown higher false‐negative rates in invasive cancers, with cytology cotesting improving the detection of invasive cancer 12‐15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation